Contribution to the knowledge of the bumblebee fauna of Afghanistan (Hymenoptera, Apidae, Bombus Latreille) - Guillaume Ghisbain; Paul H. Williams; Denis Michez; Michael G. Branstetter; Pierre Rasmont (ZooKeys, 2020)
Bumblebees (Hymenoptera: Apidae: genus Bombus Latreille, 1802) constitute an important group of pollinators for many wild plants and crops in north temperate regions and South America. Although knowledge of these insects has been increasing over the last decades, some geographic areas remain poorly studied and additions to the knowledge of their faunas are infrequent. Afghanistan is one example of a country that is currently underrepresented in the scientific literature despite its high species diversity. For this study, more than 420 new occurrence records were gathered for 17 bumblebee species belonging to all eight subgenera recorded in the country, including the first record of a species closely related to the B longipennis group. Additionally, the first standardized database for Afghan bees is launched, which we hope will be enriched in the future to allow further assessments of population trends for the bumblebees of Afghanistan. Finally, the previously published species records for the country are discussed considering the most recent taxonomic revisions of the genus and key perspectives are highlighted for further work in this understudied country and neighboring regions.